PEMBERDAYAAN GURU IPS SMP DALAM PEMANFAATAN MEDIA BELAJAR BERBASIS ARTIFICIAL INTELLIGENCE - M. Fashihullisan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Artificial Intelligence (AI) has brought significant changes to human life. Education should adapt to these developments by integrating AI-based learning media into the teaching and learning process. This study aims to analyze the readiness of junior high school social studies teachers to utilize AI-based learning media and to examine empowerment strategies that enable them to effectively implement such media in their instructional practices. The research employed a qualitative descriptive approach, with the participants consisting of teachers from a public junior high school in Pacitan Regency, Indonesia. The findings indicate that teachers are not yet adequately prepared to utilize AI-based learning media. Therefore, teacher empowerment is necessary to enhance their capacity to integrate AI-based learning media, particularly through the application of Communicative Action Theory.